2018
DOI: 10.1111/cdev.13162
|View full text |Cite
|
Sign up to set email alerts
|

Paracosms: The Imaginary Worlds of Middle Childhood

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…That said, there were positive correlations between scores on three creativity tasks that involved a more social element -story stem, draw a pretend person, and social consequences. Although Taylor et al (2020) generally did not find any gender differences, girls produced more creative story endings than boys, and age was correlated with the alternate uses divergent thinking task. These findings thus lend support to the view that creativity is domain specific rather than domain general, and that FO may be differentially related to different domains of creativity (Baer, 2012;Kaufman, 2012).…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…That said, there were positive correlations between scores on three creativity tasks that involved a more social element -story stem, draw a pretend person, and social consequences. Although Taylor et al (2020) generally did not find any gender differences, girls produced more creative story endings than boys, and age was correlated with the alternate uses divergent thinking task. These findings thus lend support to the view that creativity is domain specific rather than domain general, and that FO may be differentially related to different domains of creativity (Baer, 2012;Kaufman, 2012).…”
mentioning
confidence: 69%
“…The strength of the relation between FO and creativity may, however, be dependent on other factors, including what domain of creativity is assessed in a creative thinking task, as well as individual differences, such as age or gender. Taylor et al (2020) found evidence suggesting a link between FO and creativity for some of their creativity tasks in 8-to 12-yearolds but not for others. They found that children who invented imaginary worlds, or paracosms, provided a more creative ending to a story stem than children who had not invented paracosms.…”
mentioning
confidence: 88%
“…In developmental research, the imagination is often linked to the generation of creative or unusual possibilities and children's early capacity for make-believe is seen as a potential index of those generative abilities. In line with this perspective, researchers have documented intriguing individual differences among children in their engagement with imaginary companions and imaginary worlds, and examined potential links to variation in social understanding, story-telling, and divergent thinking (Taylor, 1999;Taylor & Carlson, 1997;Taylor, Mottweiler, Aguiar, Naylor, & Levernier, 2020;Trionfi & Reese, 2009). This focus on the imagination of young children, as exemplified by their pretend play, is sometimes accompanied by concerns that an overly academic curriculum, with limited opportunities for make-believe, might stifle the development of children's imagination (Lillard & Taggart, 2019;Weisberg, Hirsh-Pasek, Golinkoff, Kittredge, & Klahr, 2016).…”
mentioning
confidence: 99%
“…Researchers are starting to believe future creative success can be predicted by this uncommon childhood activity (Taylor, Mottweiler, Aguiar, Naylor, and Levernier [2018] discovered the phenomenon in less than one in five 8‐12‐year‐olds). But it took a long time to posit that theory.…”
Section: What Is a Paracosm?mentioning
confidence: 99%
“…In short, what has been discovered about creative thinking in all children? Taylor et al (2018), in their first study of paracosms in middle childhood, concluded their presence in 8–12‐year‐old‐children was 17%. Interestingly, 83% of these children who created paracosms also had imaginary companions, though Taylor et al do not try to draw any causal relationships.…”
Section: History Of Paracosm Researchmentioning
confidence: 99%